Overall design of the Danish National transport model - Rich, Jeppe; Nielsen, Otto Anker; Brems, Camilla; Hansen, Christian Overgaard (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
The objective of the new Danish national transport model is to establish a unified reference model, which will form a new basis for transport policy analysis in Denmark. There are a number of important benefits by developing a single model framework rather than relying on a variety of regional models. Firstly, as different projects is compared using the same model, potential model bias will be ruled out. Secondly, as more resources can be put into the development of a single model, it can also be more comprehensive and advanced in a number of respects. Thirdly, it becomes much easier to maintain and update the data foundation, which is a very important issue in model development. The aim of the present paper is to outline the general model structure and to discuss how the model will be able to address a range of scenarios. More specifically, we will discuss how different model components are linked and briefly present the forecast methodology.